An engineering rock mass quality classification system for deep-buried hard rock tunnels - Wu, Zhijue; Wu, Longliang; Lin, Tao; Niu, Wen-Jing (Frontiers in Earth Science, 2024)
Rockburst events occur sporadically following tunnel excavation in deep-buried hard rock formations. These failures in the surrounding rock masses are primarily induced by high ground stress, rendering conventional rock mass quality classification systems less applicable. This study discusses the limitations of existing rock mass quality classification systems when applied to deepburied hard rock tunnels. A rockburst intensity tendency index, quantified through micro-seismic (MS) monitoring, is introduced and integrated into the Rock Mass Rating (RMR) system, resulting in the development of an engineering rock mass quality classification system for deep-buried hard rock tunnels (DHRT-RMR). The development process involves: (i) selecting input parameters, including the rockburst intensity tendency index, and defining their weightings using the Analytic Hierarchy Process (AHP); and (ii) establishing the DHRT-RMR system based on the principles of the RMR system. The rockburst intensity tendency index, DHRT-RMR system, and RMR system are then applied to two test sites selected from a tunnel in southwest China. Results indicate that the standalone use of RMR or the rockburst intensity tendency index is limited in engineering rock mass classification for deep-buried hard rock tunnels. However, the DHRT-RMR system accurately assesses rock mass qualities in such tunnels.